2022
DOI: 10.2967/jnmt.121.262900
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Convolutional Neural Networks for Fast Determination of Whole-Body Metabolic Tumor Burden in Pediatric Lymphoma

Abstract: F-FDG PET/CT quantification of whole-body tumor burden in lymphoma is not routinely performed because of the lack of fast methods. Although the semiautomatic method is fast, it is not fast enough to quantify tumor burden in daily clinical practice. Our purpose was to evaluate the performance of convolutional neural network (CNN) software in localizing neoplastic lesions in whole-body 18 F-FDG PET/CT images of pediatric lymphoma patients. Methods: The retrospective image dataset, derived from the data pool of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…demonstrated application of DL multi‐focal segmentation in reliably determining MTV and TLG in lymphoma and found that it reduced time to 18% of manual approaches. In similar research, 18 F FDG PET MTV and TLG in paediatric lymphoma patients were highly correlated for computer‐assisted versus DL segmentation but showed faster processing time for DL with DL taking just 1.5% of the processing time of computer‐assisted approaches (mean of 19 sec versus 21.6 min) 30 . DL has also been reported to effectively localise lesions and then classify as suspicious or otherwise in lung cancer and lymphoma 31 .…”
Section: Deep Molecular Radiomicsmentioning
confidence: 83%
See 1 more Smart Citation
“…demonstrated application of DL multi‐focal segmentation in reliably determining MTV and TLG in lymphoma and found that it reduced time to 18% of manual approaches. In similar research, 18 F FDG PET MTV and TLG in paediatric lymphoma patients were highly correlated for computer‐assisted versus DL segmentation but showed faster processing time for DL with DL taking just 1.5% of the processing time of computer‐assisted approaches (mean of 19 sec versus 21.6 min) 30 . DL has also been reported to effectively localise lesions and then classify as suspicious or otherwise in lung cancer and lymphoma 31 .…”
Section: Deep Molecular Radiomicsmentioning
confidence: 83%
“…In similar research, 18 F FDG PET MTV and TLG in paediatric lymphoma patients were highly correlated for computer-assisted versus DL segmentation but showed faster processing time for DL with DL taking just 1.5% of the processing time of computer-assisted approaches (mean of 19 sec versus 21.6 min). 30 DL has also been reported to effectively localise lesions and then classify as suspicious or otherwise in lung cancer and lymphoma. 31 DL has also been used for auto-segmentation of metastatic deposits on bone SPECT studies to improve staging and determination of tumour burden.…”
Section: Deep Molecular Radiomicsmentioning
confidence: 99%
“…There is growing evidence for the utility of using machine learning methods for semiquantification, such as convolutional neural networks (CNN). Recent work by Etchebehere et al demonstrated clearly that the determination of whole body tumour burden in patients with paediatric lymphoma using CNN is fast and feasible in implementation in clinical practice [19].…”
Section: Paediatric Lymphomamentioning
confidence: 99%